Microstructure and fatigue crack growth behavior in tungsten inert gas welded DP780 dual-phase steel. (15th November 2015) - Li, Shengci; Kang, Yonglin; Zhu, Guoming; Kuang, Shuang
Abstract: The purpose of this study was to evaluate microstructural and mechanical change of DP780 steel after tungsten inert gas (TIG) welding and the influence of notch locations on the fatigue crack growth (FCG) behavior. The tempering of martensite in the sub-critical heat affected zone (HAZ) resulted in a lower hardness (~ 220 HV) compared to the base material (~ 270 HV), failure was found to originate in the soft HAZ during tensile test. The fusion zone (FZ) consisted of martensite and some acicular ferrite. The joint showed a superior tensile strength with a joint efficiency of 94.6%. The crack growth path of HAZ gradually deviated towards BM due to the asymmetrical plastic zone at the crack tip. The FCG rate of the crack transverse to the weld was fluctuant. The Paris model can describe the FCG rate of homogeneous material rather well, but it cannot precisely represent the FCG rate of heterogeneous material. The fatigue fracture surface showed that the stable expanding region was mainly characterized by typical fatigue striations in conjunction with secondary cracks; the rapid expanding region contained quasi-cleavage morphology and dimples. However, ductile fracture mechanism predominated with an increasing stress intensity factor range (Δ K ). The final unstable failure fractograph was subtotal dimples. Graphical abstract: Highlights: Notch locations affect the fatigue crack growth (FCG) behavior of the investigated dual phase steel. The Paris model cannot precisely describe the FCG rate of heterogeneous material. Ductile fracture mechanism predominates with an increasing Δ K at the rapid expanding region.